2014
DOI: 10.1097/mao.0000000000000431
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Unilateral Sudden Deafness Improves Tinnitus and Speech Comprehension

Abstract: Cochlear implantation in unilateral sudden hearing loss with a normal functioning contralateral ear might prove to be an effective therapy. Tinnitus is reduced as is the signal-to-noise ratio, which still allows 50% speech discrimination. All patients felt that they localized sound better, and most felt that they understood speech better. Further studies should be conducted to compare the success of hearing rehabilitation of cochlear rehabilitation and traditional modalities such as contralateral routing of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 21 publications
4
62
0
2
Order By: Relevance
“…Never the less, this percentage is under the expected improvement in unilaterally implanted deaf people without vestibular schwannoma operation 33 . This difference may be due to the small numbers of patients included in our study due to small number of patients receiving cochlear implantation after vestibular schwannoma removal.…”
Section: Discussionmentioning
confidence: 99%
“…Never the less, this percentage is under the expected improvement in unilaterally implanted deaf people without vestibular schwannoma operation 33 . This difference may be due to the small numbers of patients included in our study due to small number of patients receiving cochlear implantation after vestibular schwannoma removal.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, tinnitus can also be a complication after cochlear implantation [Di Nardo et al, 2007;Postelmans et al, 2007;Hou et al, 2010], possibly related to cochlear damage due to the surgery [Nordfalk et al, 2014;Todt et al, 2014]. Van de Heyning et al [2008] reported the first results of cochlear implantation in an attempt to treat tinnitus in single-sided deafness (SSD), after which many studies followed on tinnitus suppression in SSD [Kleinjung et al, 2009;Arndt et al, 2010;Buechner et al, 2010;Palau et al, 2010;Jacob et al, 2011;Kleine Punte et al, 2011;Firszt et al, 2012b;Mendes et al, 2012;Ramos et al, 2012;Hansen et al, 2013;Távora-Vieira et al, 2013 and reviewed by Arts et al, 2012;Blasco and Redleaf, 2014;Tokita et al, 2014;Vlastarakos et al, 2014;van Zon et al, 2015]. As a common conclusion it can be stated that cochlear implantation is a viable treatment option for tinnitus in SSD.…”
Section: Introductionmentioning
confidence: 99%
“…when speech is directed towards the implanted ear and noise towards the non-implanted ear (Blasco and Redleaf, 2014;van Zon et al, 2015). In this listening situation, use of the implant allows the patient to access a copy of the speech signal that is less degraded than that which is accessible using their better ear alone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were identified from existing systematic reviews that assessed the evidence for cochlear implantation in adults with unilateral deafness or highly asymmetric hearing loss (Blasco and Redleaf, 2014;Kitterick et al, 2015;van Zon et al, 2015). These reviews were identified through title and abstract searches of the Medline, EMBASE, PubMed, and Cochrane Library databases.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation